Extracurricular Program Management at State Junior High School 7 in Jambi City - Munandar, Aris; Hidayat, Wahyu (El-Idare: Journal of Islamic Education Management, 2023)
Education plays a crucial role in shaping character and advancing the nation. This research focuses on the management of extracurricular programs at State Junior High School 7 in Kota Jambi, with an emphasis on planning, implementation, and evaluation. Using a descriptive qualitative approach, the study involves the researcher as the main instrument, utilizing interviews, observations, and documentation for data collection. The goal is to describe the management and evaluation of extracurricular activities while identifying implementation barriers. Findings indicate that extracurricular planning is based on active participation, teamwork, and a focus on the process. Successful program implementation creates an environment supportive of character development and student achievement. Periodic evaluations, involving photo documentation, enable continuous improvement. Effective communication between the school and extracurricular supervisors is key to overcoming implementation obstacles. This research provides profound insights into effective and sustainable extracurricular management in the context of education at State Junior High School 7 in Kota Jambi.